Insecticidal Activity of Cymbopogon citratus and Melaleuca leucadendra Essential Oils and Their Joint Actions Against Spodoptera frugiperda - Syahputra, Edy; Jayuska, Afghani; Satrio, Bagus Sandi; Wibowo, Vicy Arif (AGRIVITA Journal of Agricultural Science, 2025)
A high population of Spodoptera frugiperda larvae reduces corn crop productivity. One alternative insect pest control method is the use of mixed essential oils. This research aims to evaluate the insecticidal and antifeedant activity of lemongrass (Cymbopogon citratus) and melaleuca (Melaleuca leucadendra) essential oils against S. frugiperda larvae, as well as their combined effect. The essential oils were produced using a steam distillation method.  The insecticidal activities were assayed using feeding method. The levels of essential oil concentration tested and controlled were repeated five times. The concentration-mortality relationship was analyzed using probit. Antifeedant activity tested by choice and no-choice at sub-lethal concentrations equivalent to LC10,LC25, and LC50. The test results showed that insecticidal activity of the essential oils of C. citratus higher than M leucadendra. Both essential oils showed LC50 values of 0.9% and 1.1% respectively. Both essential oils also showed antifeedant activity. In the choice test and no-choice test at LC10,LC25, and LC50 showed feeding inhibition of 23.7%-56.7%. The mixture of the two essential oils has a strongly synergistic action with an LC50 of 0.15% and a combination index of 0.15. Further research is needed to evaluate the extract mixture in the field.